Positive electrode active material, battery, and method for producing positive electrode active material

By using the combination of compound A and compound B in the positive electrode active material, the M element does not react with the Li element, and the problem of increasing electron resistance caused by M element in the prior art is solved, and the effect of low battery resistance is achieved.

CN119920862APending Publication Date: 2025-05-02TOYOTA JIDOSHA KK
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411507349.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-10-31
Filing Date
2024-10-28
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The M element added to the existing positive electrode active material exists as a Li compound, which leads to an increase in the electron resistance and makes it difficult to effectively reduce the battery resistance.

Method used

The positive electrode active material consisting of compound A represented by LixNiaCobMncOy and compound B represented by MdOe was used, and the presence ratio of elements with an ion radius α in the particles of compound B was more than 45 mol%, and the area ratio X was 0.8%≤X≤19.6%, to ensure that the M element does not react with the Li element and reduce the battery resistance.

Benefits of technology

By sufficiently presenting M element that does not react with Li element in the positive electrode active material, the resistance of the battery is significantly reduced and the performance of the battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119920862A_ABST
    Figure CN119920862A_ABST
Patent Text Reader

Abstract

The invention relates to a positive electrode active material, a battery, and a method for manufacturing the positive electrode active material. Provided is a positive electrode active material capable of achieving low battery resistance. A positive electrode active material having particles of a compound A having a composition represented by LixNiaCobMncOy and particles of a compound B having a composition represented by MdOe, in the particles of the compound B, the abundance ratio of an element having an ion radius alpha of # imgabs0 # is 45 mol% or more, and the content of the element having an ion radius alpha of # imgabs0 # relative to the total of the particles of the compound A and the particles of the compound B is 5 mol% or more. The area ratio X of the particles of the compound B is 0.8% < = X < = 19.6%. Wherein 0.1 < = x < = 1.5, 0.5 < = a < = 1.0, 0 < = b < = 0.3, 0 < = c < = 0.3, a + b + c = 1.0, and 1.5 < = y < = 2.1, 0.001 < = d < = 0.2, and 0.002 < = e < = 0.4, and M represents at least one element selected from the group consisting of Ti, Zr, Ta, Pr, K, La, Ba, Y, Sr, Ce, Se, Hf, and Rh.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a positive electrode active material, a battery, and a method for producing the positive electrode active material. Background Art

[0002] Conventionally, attempts have been made to add various additional elements to positive electrode active materials used in batteries in order to improve the resistance characteristics of the batteries.

[0003] For example, Patent Document 1 discloses a surface-modified lithium-containing composite oxide for a positive electrode of a lithium-ion secondary battery, wherein the surface-modified lithium-containing composite oxide is a composite oxide having a general formula (Li 1+x (Co (1-a-b-m) Ni a Al b M m ) 1-x O 2-(f / 2) F f ) is modified with a surface modification compound containing at least one element selected from group S1 and group S2, group S1 is a group consisting of Al, Zr, Ti, Mg, Zn, Nb, Mo, Ta, W and rare earth, group S2 is a group consisting of F, P and S, M is at least one element selected from transition metals other than Co and Ni, Sn, Ge, Na, K, B, C, Si, P, S, Zn, Ga, Bi, second group elements and rare earth, -0.05≤x≤0.05, 0<a≤0.25, 0<b≤0.05, 0≤m≤0.04, 0≤f≤0.05.

[0004] In addition, Patent Document 2 discloses a positive electrode active material for a lithium secondary battery, which comprises a lithium nickel cobalt manganese oxide and metal oxide particles, wherein the lithium nickel cobalt manganese oxide comprises secondary particles having at least one primary particle aggregated therein and is represented by Chemical Formula 1 (Li a [Ni x Co y Mn z ] t M 1-t O 2-p X p ) indicates that the metal oxide particles are located inside the secondary particles and have an average particle size (D50) of nanometer size. In the chemical formula 1, M is any element selected from the group consisting of Al, Mg, Sn, Ca, Ge, Ga, B, Ti, Mo, Nb and W, X is any element selected from the group consisting of F, N and P, and a is 0.8≤a≤1.3, 0.6≤x≤0.95, 0<y≤0.2, 0<z≤0.2, x+y+z=1, 0≤t≤1, and 0≤p≤0.1.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent No. 6359323

[0008] Patent Document 2: Japanese Patent No. 7300792 Summary of the invention

[0009] Problems to be solved by the invention

[0010] In the conventional positive electrode active material, an additional element (e.g., an element represented by M (M element)) is added to the positive electrode active material. Conventionally, the additional element (M element) exists in the particles of the positive electrode active material as a Li compound that reacts with the Li element, and the M element that reacts with the Li element tends to increase the electronic resistance.

[0011] Therefore, there is a need for a positive electrode active material that can further reduce battery resistance.

[0012] The present disclosure has been made in view of the above-mentioned actual situation, and an object of the present disclosure is to provide a positive electrode active material capable of achieving low battery resistance when used in a battery, a battery including the positive electrode active material, and a method for producing the positive electrode active material.

[0013] Means for solving problems

[0014] Means for solving the above-mentioned problems include the following.

[0015] <1> A positive electrode active material having: a Li x Ni a Co b Mn c O y Particles of compound A having a composition represented by M d O e A particle of compound B having a composition represented by: The presence ratio of the element is more than 45 mol%, and the area ratio X of the particles of the compound B relative to the total of the particles of the compound A and the particles of the compound B is 0.8%≤X≤19.6%. In the composition of the compound A, 0.1≤x≤1.5, 0.5≤a≤1.0, 0≤b≤0.3, 0≤c≤0.3, a+b+c=1.0, and 1.5≤y≤2.1, and in the composition of the compound B, 0.001≤d≤0.2 and 0.002≤e≤0.4, and the M represents at least one element selected from Ti, Zr, Ta, Pr, K, La, Ba, Y, Sr, Ce, Se, Hf and Rh.

[0016] <2> The positive electrode active material according to <1>, wherein the element represented by M is at least one element selected from the group consisting of Ti, Zr, Ta, Pr, K, and La.

[0017] <3> The positive electrode active material according to <2>, wherein the element represented by M is Ti.

[0018] <4> A battery comprising the positive electrode active material according to any one of <1> to <3>.

[0019] <5> A method for manufacturing a positive electrode active material, comprising: a step of preparing a solution in which raw materials containing Ni, Co and Mn are dissolved respectively; a step of adding the solution to an alkaline solution to precipitate hydroxide; a step of collecting the precipitate from the alkaline solution; a step of mixing the precipitate with a raw material containing Li to obtain a first mixture; a first calcining step of calcining the first mixture; a step of mixing a raw material containing an element represented by M with the calcined first mixture to obtain a second mixture; and a second calcining step of calcining the second mixture, wherein M is at least one element selected from the group consisting of Ti, Zr, Ta, Pr, K, La, Ba, Y, Sr, Ce, Se, Hf and Rh.

[0020] Effects of the Invention

[0021] According to the present disclosure, a positive electrode active material capable of achieving low battery resistance when used in a battery, a battery including the positive electrode active material, and a method for producing the positive electrode active material can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 It is a diagram showing a scheme of a method for producing a positive electrode active material according to an embodiment of the present disclosure. DETAILED DESCRIPTION

[0023] The following describes an embodiment as an example of the present disclosure. These descriptions and examples are illustrative of the embodiment and do not limit the scope of the invention.

[0024] In the numerical range recorded in stages in this specification, the upper limit or lower limit recorded in one numerical range can be replaced by the upper limit or lower limit of the numerical range recorded in another stage. In addition, in the numerical range recorded in this specification, the upper limit or lower limit of its numerical range can be replaced by the value shown in the embodiment.

[0025] Each component may contain a plurality of substances corresponding to the component.

[0026] When referring to the amount of each component in a composition, if there are plural substances corresponding to each component in the composition, unless otherwise specified, it means the total amount of the plural substances present in the composition.

[0027] The term "process" does not only refer to an independent process, but also includes a process that cannot be clearly distinguished from other processes as long as the intended effect of the process is achieved.

[0028] <Positive electrode active material>

[0029] The positive electrode active material according to the embodiment of the present disclosure has: x Ni a Co b Mn c O y A compound A having a composition represented by d O e Represents the composition of compound B.

[0030] In the particles of compound B, the ionic radius α is The presence ratio of the element is 45 mol% or more.

[0031] Furthermore, the area ratio X of the particles of the compound B relative to the total of the particles of the compound A and the particles of the compound B is 0.8%≤X≤19.6%.

[0032] (Wherein, in the composition of compound A, 0.1≤x≤1.5, 0.5≤a≤1.0, 0≤b≤0.3, 0≤c≤0.3, a+b+c=1.0, and 1.5≤y≤2.1. In addition, in the composition of compound B, 0.001≤d≤0.2, and 0.002≤e≤0.4, and M represents at least one element selected from Ti, Zr, Ta, Pr, K, La, Ba, Y, Sr, Ce, Se, Hf, and Rh.)

[0033] In addition, the ratio x of the Li element, the ratio a of the Ni element, the ratio b of the Co element, the ratio c of the Mn element, and the ratio y of the O element contained in the compound A, and the ratio d of the M element and the ratio e of the O element contained in the compound B represent the ratios in the entire particles of the compound A and the particles of the compound B. That is, the ratios x, a, b, c, and y represent the ratios in the entire compound A and the compound B, not the ratios in only the compound A. In addition, the ratios d and e represent the ratios in the entire compound A and the compound B, not the ratios in only the compound B.

[0034] So far, for the purpose of improving the resistance characteristics of the battery, etc., an additional element (i.e., the element represented by M, hereinafter also referred to as "M element") is added to the positive electrode active material. Furthermore, in the past, the additional element (M element) existed in the particles of the positive electrode active material as a Li compound reacted with the Li element.

[0035] However, the M element reacting with the Li element tends to increase the electronic resistance, and further improvement is required from the viewpoint of reducing the battery resistance when the positive electrode active material is used in a battery.

[0036] The positive electrode active material according to the embodiment of the present disclosure includes active material particles (ie, particles of compound A) and an oxide containing element M (M d O e ) (i.e., particles of compound B) are these two types of particles.

[0037] Furthermore, in the particles of compound B, the ionic radius α is The presence ratio of the elements is more than 45 mol%, in other words, it means that the particles of compound B fully contain the elements of Ti, Zr, Ta, Pr, K, La, Ba, Y, Sr, Ce, Se, Hf and Rh.

[0038] Furthermore, the area ratio X is in the range of 0.8%≤X≤19.6%, which means that the M element that has not reacted with the Li element (that is, the M element contained in the particles of the compound B) is sufficiently present in the positive electrode active material.

[0039] Thus, the M element having low electronic resistance and not reacting with the Li element is sufficiently present between particles of the positive electrode active material, and thus the battery resistance can be reduced.

[0040] Next, the positive electrode active material according to the embodiment of the present disclosure will be described in detail.

[0041] (Particles of Compound A)

[0042] The positive electrode active material according to the embodiment of the present disclosure has: x Ni a Co b Mn c O y Particles of compound A having a composition represented by . The particles of compound A are particles containing a positive electrode active material.

[0043] (In the composition of compound A, 0.1≤x≤1.5, 0.5≤a≤1.0, 0≤b≤0.3, 0≤c≤0.3, a+b+c=1.0, and 1.5≤y≤2.1.)

[0044] In the composition of the particles of compound A, from the viewpoint of resistance characteristics of the battery, etc., the ratio x of Li is 0.1 to 1.5, preferably 0.3 to 1.4, and more preferably 0.5 to 1.2.

[0045] The ratio a of Ni is 0.5 or more and 1.0 or less, preferably 0.6 or more and 0.9 or less, and more preferably 0.7 or more and 0.8 or less.

[0046] The ratio b of Co is 0 to 0.3, preferably 0 to 0.2, and more preferably 0.1 to 0.2.

[0047] The ratio c of Mn is 0 to 0.3, preferably 0 to 0.2, and more preferably 0.1 to 0.2.

[0048] In addition, the total ratio (a+b+c) of Ni, Co and Mn is 1.0.

[0049] The ratio y of O is 1.5 or more and 2.1 or less, preferably 1.7 or more and 2.1 or less, and more preferably 1.9 or more and 2.0 or less.

[0050] As described above, the ratios x, a, b, c, and y in compound A represent the ratios in the particles of compound A and the particles of compound B as a whole (the ratios in the total number of particles of compound A and particles of compound B).

[0051] (Particles of Compound B)

[0052] The positive electrode active material according to the embodiment of the present disclosure has: d O e Represents the composition of particles of compound B.

[0053] (In the composition of compound B, 0.001≤d≤0.2, and 0.002≤e≤0.4. M represents at least one element selected from Ti, Zr, Ta, Pr, K, La, Ba, Y, Sr, Ce, Se, Hf and Rh.)

[0054] Compound B contains at least one element selected from Ti, Zr, Ta, Pr, K, La, Ba, Y, Sr, Ce, Se, Hf and Rh as an additive element (M element). By containing the above-listed elements as oxides in the particles of compound B as additive elements, the battery resistance can be reduced when the positive electrode active material is used in a battery.

[0055] Furthermore, from the viewpoint of reducing battery resistance, compound B preferably contains at least one element selected from Ti, Zr, Ta, Pr, K and La as an additional element (M element), and more preferably contains Ti.

[0056] In the composition of the particles of compound B, from the viewpoint of the resistance characteristics of the battery, etc., the ratio d of M is 0.001 to 0.2, preferably 0.01 to 0.15, and more preferably 0.05 to 0.1.

[0057] The ratio e of O is 0.002 or more and 0.4 or less, preferably 0.01 or more and 0.3 or less, and more preferably 0.03 or more and 0.2 or less.

[0058] As described above, the ratios d and e in compound B represent the ratios in the particles of compound A and the entire particles of compound B (the ratios in the entire particles of compound A and the entire particles of compound B).

[0059] In the particles of compound B, the ionic radius α is The proportion of the element (hereinafter also referred to as "specific element") is 45 mol% or more. The elements (specific elements) of the compound B include Ti, Zr, Ta, Pr, K, La, Ba, Y, Sr, Ce, Se, Hf and Rh as the above-mentioned additive elements (M elements). That is, the abundance ratio of the specific elements in the particles of the compound B becomes an indicator of the abundance ratio of the M elements contained in the particles of the compound B.

[0060] In the particles of compound B, the ionic radius α is The abundance ratio of the element (specific element) is 45 mol % or more, more preferably 50 mol % or more and 90 mol % or less, and more preferably 55 mol % or more and 87 mol % or less from the viewpoint of the resistance characteristics of the battery.

[0061] (Area ratio X of particles of compound B)

[0062] In the positive electrode active material according to the embodiment of the present disclosure, the area ratio X of the particles of compound B relative to the total of the particles of compound A and the particles of compound B is 0.8%≤X≤19.6%. By making the area ratio X greater than 0.8%, the M element that does not react with the Li element (i.e., the M element contained in the particles of compound B) is sufficiently present in the positive electrode active material, and the battery resistance can be reduced. On the other hand, by making the area ratio X less than 19.6%, the particles of compound A (i.e., the particles containing the positive electrode active material) are sufficiently present, and the function as a positive electrode can be fully exerted.

[0063] From the viewpoint of the resistance characteristics of the battery and the function of the positive electrode, the area ratio X of the particles of the compound B is preferably 2.0%≤X≤15.0%, and more preferably 4.0%≤X≤10.0%.

[0064] [Measurement of Existence Ratio of Specific Elements and Area Ratio X of Particles of Compound B]

[0065] The ionic radius α of the particle of compound B is The abundance ratio of the element (specific element) and the area ratio X of the particles of the compound B relative to the total of the particles of the compound A and the particles of the compound B are measured by the following method.

[0066] First, for the positive electrode active material to be measured, data is obtained by using a scanning electron microscope (SEM) with 10 particles entering the field of view, and the operation is repeated until data for 100 particles can be obtained. Secondly, a circular analysis area along the periphery of each particle is set and obtained by using energy dispersive X-ray fluorescence spectroscopy (EDX) for quantitative composition analysis.

[0067] The ionic radius α of the particles of compound B was found to be The presence ratio of an element (specific element).

[0068] In addition, the ion radius was calculated from the data of the set circular analysis area along the outer circumference of each particle. The area ratio (area %) of particles (ie, particles of compound B) in which the existence ratio of the element (specific element) is 45 mol % or more.

[0069] <Method for producing positive electrode active material>

[0070] Next, a method for producing a positive electrode active material according to an embodiment of the present disclosure will be described. The positive electrode active material according to the embodiment of the present disclosure described above can be produced by the method for producing a positive electrode active material according to an embodiment of the present disclosure described below.

[0071] The method for producing a positive electrode active material according to an embodiment of the present disclosure includes the following steps (1) to (7).

[0072] (1) Step of preparing a solution in which raw materials containing Ni, Co, and Mn are dissolved (raw material dissolution)

[0073] (2) Adding the above solution to an alkaline solution to precipitate the hydroxide (crystallization)

[0074] (3) A step of collecting a precipitate from the alkaline solution

[0075] (4) A step of mixing the precipitate with a raw material containing Li to obtain a first mixture (Li raw material addition)

[0076] (5) First calcination step of calcining the first mixture (first calcination)

[0077] (6) A step of mixing a raw material containing an element represented by M with the fired first mixture to obtain a second mixture (M raw material addition)

[0078] (7) A second calcining step of calcining the second mixture (second calcination)

[0079] (Wherein, M represents at least one element selected from the group consisting of Ti, Zr, Ta, Pr, K, La, Ba, Y, Sr, Ce, Se, Hf and Rh.)

[0080] In the method for manufacturing a positive electrode active material involved in an embodiment of the present disclosure, after adding a raw material containing Li and performing a first calcination, a raw material containing an element represented by M is added and a second calcination is performed. The M element can exist as an oxide (i.e., particles of compound B) without becoming a Li compound, and a positive electrode active material with low resistance can be obtained.

[0081] Below, these steps are divided into Figure 1 The scheme shown is described.

[0082] (1) Step of preparing a solution in which raw materials containing Ni, Co, and Mn are dissolved

[0083] A solution ( Figure 1 The process of “dissolving raw materials” shown in FIG.

[0084] For example, a solution can be prepared by dissolving a raw material containing Ni, a raw material containing Co, and a raw material containing Mn in a solvent such as water. The concentration of the solution is preferably in the range of 10 to 40 mass %. The ratio of Ni / Co / Mn is preferably 1.0 / 0.8 to 1.2 / 0.8 to 1.2 (atomic %) relative to Ni: 1.0.

[0085] Examples of the raw material containing Ni include sulfates such as NiSO 4 , examples of the raw material containing Co include sulfates such as CoSO 4 , and examples of the raw material containing Mn include sulfates such as MnSO 4 .

[0086] (2) Step of adding a solution to an alkaline solution to precipitate a hydroxide

[0087] Secondly, add the solution to the alkaline solution to precipitate the hydroxide ( Figure 1 The crystallization step is shown in FIG. 1 ). As a result, particles containing hydroxides of Ni, Co, and Mn are crystallized and obtained as a precipitate. In this step, for example, the alkaline solution in which the hydroxides are precipitated is controlled to a certain pH (e.g., pH 10 to 12), while the solution and NH3 are added dropwise, thereby precipitating the hydroxides of the transition metals.

[0088] (3) Step of collecting precipitate from alkaline solution

[0089] Next, the precipitate is collected (extracted) from the alkaline solution.

[0090] As a method for collecting particles of the precipitate, for example, filtering and water washing methods can be cited. The following method can be cited: first, the precipitate (particles) are taken out by filtering, washed with water, and then the washed liquid is filtered to take out the precipitate (particles). In addition, the washed precipitate (particles) can be further dried.

[0091] (4) A step of mixing the precipitate and a raw material containing Li to obtain a first mixture

[0092] Next, the collected precipitate (particles) is mixed with a raw material containing Li to obtain a first mixture ( Figure 1 For example, the collected precipitate particles and the raw material containing Li can be mixed in a mortar.

[0093] Examples of raw materials containing Li include Li 2 CO 3 and LiOH.

[0094] (5) First calcining step of calcining the first mixture

[0095] Next, the collected precipitate (particles) and the first mixture containing the raw material of Li are calcined ( Figure 1 The first mixture may be fired in a firing furnace (muffle furnace, etc.). The firing conditions may be, for example, a temperature of 800° C. to 1100° C., an oxygen atmosphere, and a time of 5 to 20 hours.

[0096] Furthermore, the first mixture after the first calcination may be crushed in order to make the first mixture have a predetermined particle size. Examples of the crushing method include crushing using a pulverizer (eg, a jet mill).

[0097] (6) A step of mixing a raw material containing an element represented by M with the fired first mixture to obtain a second mixture

[0098] Next, the first mixture after the first calcination is mixed with a raw material containing an element represented by M to obtain a second mixture ( Figure 1 For example, the first mixture after the first firing and the raw material containing M can be mixed in a mortar.

[0099] As raw materials containing M (i.e., at least one element selected from Ti, Zr, Ta, Pr, K, La, Ba, Y, Sr, Ce, Se, Hf and Rh), oxides of each element (for example, TiO2, ZrO2, Ta2O5, Pr2O3, La2O3 and K2O) and the like can be listed.

[0100] (7) Second calcining step of calcining the second mixture

[0101] Next, a second mixture containing a raw material containing an element represented by M is calcined ( Figure 1 The second mixture may be fired in a firing furnace (muffle furnace, etc.). The firing conditions may be, for example, a temperature of 400°C to 600°C, an oxygen atmosphere, and a time of 5 to 20 hours. The firing temperature in the second firing step is preferably a temperature lower than that in the first firing step.

[0102] Furthermore, the second mixture after the second calcination may be crushed in order to make the second mixture have a predetermined particle size. Examples of the crushing method include crushing using a pulverizer (eg, a jet mill).

[0103] Through these steps, the positive electrode active material according to the embodiment of the present disclosure having particles of compound A and particles of compound B can be obtained.

[0104] <Battery>

[0105] The battery according to the embodiment of the present disclosure has the positive electrode active material according to the embodiment of the present disclosure. The battery has, for example, a negative electrode, a positive electrode, a separator, and an electrolyte.

[0106] The battery involved in the embodiment of the present disclosure is preferably a liquid battery having a liquid electrolyte, or a solid battery having a solid electrolyte. In addition, it can be a bipolar battery having a positive electrode active material layer and a negative electrode active material layer on both sides of a collector having the functions of a positive electrode collector and a negative electrode collector.

[0107] (positive electrode)

[0108] The positive electrode includes, for example, a positive electrode current collector and a positive electrode active material layer fixed on the positive electrode current collector.

[0109] The positive electrode active material layer contains the positive electrode active material according to the embodiment of the present disclosure as the positive electrode active material. The details of the positive electrode active material have been described above, so they are omitted here.

[0110] The positive electrode active material layer may include a conductive material in addition to the positive electrode active material, and further, may include other components, such as a binder, various additives, etc. As the conductive material, for example, graphitizable carbon such as difficult graphitization carbon, acetylene black, carbon black, graphite, etc. can be listed. As the binder, for example, a halogenated vinyl resin such as polyvinylidene fluoride (PVdF) can be exemplified.

[0111] The positive electrode current collector is preferably a conductive member made of a metal with good conductivity (such as aluminum). Alternatively, a current collector having the functions of a positive electrode current collector and a negative electrode current collector (ie, a bipolar battery) may be used.

[0112] (negative electrode)

[0113] The negative electrode includes, for example, a negative electrode current collector and a negative electrode active material layer fixed on the negative electrode current collector. As the negative electrode current collector, it is preferably a conductive member composed of a metal with good conductivity (such as copper). In addition, it can be a current collector having the functions of a positive electrode current collector and a negative electrode current collector (i.e., a bipolar battery).

[0114] The negative electrode active material layer contains a negative electrode active material. As the negative electrode active material, for example, graphite-based carbons such as natural graphite, artificial graphite, and amorphous coated graphite can be exemplified. In the graphite-based carbon, the proportion of graphite is approximately 50% by mass or more, preferably 80% by mass or more. The negative electrode active material layer may be composed only of the negative electrode active material, or may contain components other than the negative electrode active material, such as a thickener, a binder, etc. as needed. As a thickener, for example, celluloses such as carboxymethyl cellulose (CMC) can be exemplified. As a binder, for example, rubbers such as styrene butadiene copolymer (SBR), halogenated vinyl resins such as polyvinylidene fluoride (PVdF) can be exemplified.

[0115] (Diaphragm)

[0116] The diaphragm (separator) is an electrically insulating porous film. The diaphragm electrically isolates the positive electrode from the negative electrode. The diaphragm may have a thickness of, for example, 5 to 30 μm. The diaphragm may be composed of, for example, a porous polyethylene (PE) film, a porous polypropylene (PP) film, and the like. The diaphragm may have a multilayer structure. For example, the diaphragm may be composed by stacking a porous PP film, a porous PE film, and a porous PP film in sequence. The diaphragm may have a heat-resistant layer on its surface. The heat-resistant layer contains a heat-resistant material. Examples of heat-resistant materials include metal oxide particles such as aluminum oxide, high melting point resins such as polyimide, and the like.

[0117] (Electrolyte)

[0118] The battery according to the embodiment of the present disclosure may be a liquid battery further comprising an electrolyte solution. A non-aqueous electrolyte solution is particularly preferred.

[0119] Solvent

[0120] The non-aqueous electrolyte solution contains a solvent (non-aqueous solvent) and an electrolyte.

[0121] Examples of the solvent (non-aqueous solvent) include ethyl carbonate (EC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), propylene carbonate (PC), fluoroethylene carbonate (FEC), N,N-diethyl-N-methyl-N-(2-methoxyethyl)ammonium bis(fluorosulfonyl)imide (DEME), 1-ethyl-3-methylimidazolium bis(fluorosulfonyl)imide (EMI), and 1-ethyl-2,3-dimethylimidazolium bis(fluorosulfonyl)imide (DEMI-FSI).

[0122] Electrolytes

[0123] As the electrolyte in the electrolytic solution, for example, Li salts can be cited. As the Li salts, lithium bis(fluorosulfonyl)imide (LiFSI), LiPF6 (lithium hexafluorophosphate), lithium tetrafluoroborate (LiBF4), Li[N(CF3SO2)2], etc. can be cited.

[0124] The amount of the electrolyte may be, for example, 1.0 to 2.0 mol / L, preferably 1.0 to 1.5 mol / L.

[0125] In addition to the solvent and the electrolyte, the electrolyte may also contain various additives, such as a thickener, a film-forming agent, a gas generator, etc. The electrolyte is typically a non-aqueous electrolyte that is liquid at room temperature (e.g., 25±10°C). The electrolyte is typically liquid in the battery's operating environment (e.g., a temperature environment of -20 to +60°C).

[0126] (use)

[0127] Examples of uses of the battery include power sources for hybrid electric vehicles (HEV), plug-in hybrid electric vehicles (PHEV), and battery electric vehicles (BEV).

[0128] Example

[0129] The present disclosure will be described below based on examples, but the present disclosure is not limited to these examples.

[0130] <Example 1>

[0131] (Synthesis of positive electrode active material)

[0132] A positive electrode active material having particles of compound A and particles of compound B was synthesized by the following method. The particles of compound A have particles composed of Li x Ni a Co b Mnc O y The composition represented by and x, a, b, c and y are the ratios shown in Table 1, the particles of the compound B have a composition of M d O e The composition represented by d and e were in the ratios shown in Table 1, and as the element represented by M, the elements described in Table 1 were used.

[0133] ·Raw material solution

[0134] NiSO4, CoSO4 and MnSO4 were dissolved in ion exchange water to obtain a raw material solution. The ratio of Ni / Co / Mn was 1 / 1 / 1 (atomic %) and the concentration of the aqueous solution was 30 mass %.

[0135] ·Crystallization

[0136] A certain amount of NH3 aqueous solution is placed in a reaction container, and nitrogen substitution is performed while stirring with a stirrer. NaOH is added to the reaction container to make the pH alkaline. Next, while controlling the pH in the reaction container to a certain value (pH 10-12), the raw material solution and NH3 are dripped to precipitate the transition metal hydroxide.

[0137] Washing, filtering, drying

[0138] The precipitated transition metal hydroxide is taken out by filtration, ion exchange water is added, stirred with a spoon to disperse it, and washed with water.

[0139] Next, the washed liquid is filtered to take out the transition metal hydroxide.

[0140] Next, the filtered transition metal hydroxide was dried at 120° C. for 16 hours to evaporate water.

[0141] ·Li raw material mixing

[0142] The dried transition metal hydroxide is mixed with Li 2 CO 3 and LiOH as Li raw materials in a mortar.

[0143] Burn 1 and Shatter 1

[0144] The mixture of transition metal hydroxide and Li raw material is calcined in a calcination furnace (muffle furnace) at 800° C. in an oxygen atmosphere for 10 hours (calcination 1). Next, the calcined mixture is crushed by a pulverizer (jet mill) to a predetermined particle size (crushing 1).

[0145] Mixing of raw materials

[0146] The crushed mixture was mixed with TiO2 as the M raw material in a mortar.

[0147] Burn 2 and Shatter 2

[0148] The crushed mixture and the M raw material (TiO2) are calcined in a calcining furnace (muffle furnace) at 400°C for 10 hours (calcination 2). Next, the calcined mixture is crushed in a pulverizer (jet mill) to a predetermined particle size (crushing 2).

[0149] In this way, the positive electrode active material of Example 1 including particles of the compound A and particles of the compound B was obtained.

[0150] <Examples 2 to 4>

[0151] In Example 1, except that the ratio of the M element (Ti) to O in the particles of the compound B was adjusted to the ratio described in Table 1, the positive electrode active material of each example was obtained in the same manner as in Example 1.

[0152] <Examples 5 to 9>

[0153] The positive electrode active materials of each example were obtained in the same manner as in Example 1, except that the M raw material in Example 1 was changed from TiO2 to ZrO2 (Example 5), Ta2O5 (Example 6), Pr2O3 (Example 7), La2O3 (Example 8) and K2O (Example 9).

[0154] <Comparative Example 1>

[0155] (Synthesis of positive electrode active material)

[0156] A positive electrode active material having particles of compound A was synthesized by the following method. The particles of compound A have Li x Ni a Co b Mn c O y denoted by , and x, a, b, c and y are the ratios shown in Table 1.

[0157] In Example 1, a positive electrode active material of Comparative Example 1 was obtained in the same manner as in Example 1, except that the step of “mixing M raw materials” and the step of “calcining 2 and crushing 2” were not performed.

[0158] <Comparative Example 2>

[0159] (Synthesis of positive electrode active material)

[0160] A positive electrode active material having particles of compound A was synthesized by the following method. The particles of compound A have Li x Ni a Co b Mnc M d O y The composition represented by , x, a, b, c, d, and y had the ratios shown in Table 1, and as the element represented by M, the elements described in Table 1 were used.

[0161] ·Raw material solution

[0162] NiSO4, CoSO4 and MnSO4 were dissolved in ion exchange water to obtain a raw material solution. The ratio of Ni / Co / Mn was 1 / 1 / 1 (atomic %), and the concentration of the aqueous solution was 30 mass %.

[0163] ·Crystallization

[0164] A certain amount of NH3 aqueous solution is placed in a reaction container, and nitrogen substitution is performed while stirring with a stirrer. NaOH is added to the reaction container to make the pH alkaline. Next, while controlling the pH in the reaction container to a certain value (pH 10-12), the raw material solution and NH3 are dripped to precipitate the transition metal hydroxide.

[0165] Washing, filtering, drying

[0166] The precipitated transition metal hydroxide is taken out by filtration, ion exchange water is added, stirred with a spoon to disperse it, and washed with water.

[0167] Next, the washed liquid is filtered to take out the transition metal hydroxide.

[0168] Next, the filtered transition metal hydroxide was dried at 120° C. for 16 hours to evaporate water.

[0169] Mixing of Li raw material and M raw material

[0170] The dried transition metal hydroxide, Li2CO3 and LiOH as Li raw materials, and TiO2 as M raw material are mixed in a mortar.

[0171] Burn 1 and Shatter 1

[0172] The mixture of transition metal hydroxide and Li raw material is calcined in a calcination furnace (muffle furnace) at 800° C. in an oxygen atmosphere for 10 hours (calcination 1). Next, the calcined mixture is crushed by a pulverizer (jet mill) to a predetermined particle size (crushing 1).

[0173] In this manner, the positive electrode active material of Comparative Example 2 including particles of Compound A was obtained.

[0174] [Measurement of the Existence Ratio (mol%) of Specific Elements and the Area Ratio (Area%) of Particles of Compound B]

[0175] For the positive electrode active materials obtained in Examples 1 to 9, the ionic radius α of the particles of compound B was measured by the following method: The area ratio X of particles (i.e., particles of compound B) having an existence ratio of an element (specific element) and a presence ratio of the specific element of 45 mol% or more to the total area ratio X of particles of compound A and particles of compound B.

[0176] First, for the positive electrode active material, SEM was used to obtain data by allowing 10 particles to enter the field of view, and the operation was repeated until data for 100 particles could be obtained. Next, a circular analysis area along the periphery of each particle was set and obtained through EDX composition quantitative analysis. Through this EDX composition quantitative analysis, the ion radius α in the particles of compound B was found to be The results are shown in Table 1.

[0177] In addition, the ion radius was calculated from the data of the set circular analysis area along the outer circumference of each particle. The area ratio (area %) of particles (ie, particles of compound B) in which the existence ratio of the element (specific element) is 45 mol % or more.

[0178] [Production of battery cells]

[0179] A battery cell was produced using the positive electrode active material obtained in each of the Examples and Comparative Examples.

[0180] Battery cell structure

[0181] Winding cylinder

[0182] Positive electrode composition: Positive electrode active material / acetylene black (conductive material) / polyvinylidene fluoride = 88 / 10 / 2 (mass %)

[0183] Negative electrode composition: natural graphite / styrene butadiene rubber (SBR) / carboxymethyl cellulose (CMC)

[0184] Electrolyte composition: electrolyte = LiPF6 (1M), solvent = ethylene carbonate (EC) / dimethyl carbonate (DMC) / ethyl methyl carbonate (EMC) = 3 / 4 / 3 (volume %)

[0185] Electrode production

[0186] The positive electrode and the negative electrode were coated on the current collector using a film coater with a film thickness adjustment function (manufactured by Ohlgod Co., Ltd.), and dried at 80° C. for 5 minutes using a dryer to produce a battery cell.

[0187] [Initial battery resistance]

[0188] The initial battery resistance of the battery cells obtained in each example and comparative example was measured. Table 1 shows the results of the ratio (%) of the battery resistance of each example and comparative example when the battery resistance of comparative example 1 is regarded as "100%".

[0189]

Table 1

[0190]

[0191] As shown in Table 1, it can be seen that the area ratio of the particles of compound A and compound B to the total area ratio of the particles of compound A and compound B is within a range of 0.8% to 19.6%. In the positive electrode active materials of each example including the particles of compound B having an abundance ratio of the element of 45 mol % or more, the initial battery resistance can be reduced compared with the positive electrode active materials of each comparative example not including the particles of compound B.

Claims

1. A positive electrode active material having: a Li x Ni a Co b Mn c O y Particles of compound A having a composition represented by M d O e Particles of compound B representing the composition, In the particles of compound B, the ionic radius α is The presence ratio of the element is 45 mol% or more, The area ratio X of the particles of the compound B relative to the total of the particles of the compound A and the particles of the compound B is 0.8%≤X≤19.6%, In the composition of the compound A, 0.1≤x≤1.5, 0.5≤a≤1.0, 0≤b≤0.3, 0≤c≤0.3, a+b+c=1.0 and 1.5≤y≤2.1; in the composition of the compound B, 0.001≤d≤0.2 and 0.002≤e≤0.4, and M represents at least one element selected from Ti, Zr, Ta, Pr, K, La, Ba, Y, Sr, Ce, Se, Hf and Rh.

2. The positive electrode active material according to claim 1, wherein The element represented by the M is at least one element selected from the group consisting of Ti, Zr, Ta, Pr, K and La.

3. The positive electrode active material according to claim 2, wherein The element represented by the M is Ti. 4 . A battery comprising the positive electrode active material according to claim 1 .

5. A method for producing a positive electrode active material, comprising: A step of preparing a solution in which raw materials respectively containing Ni, Co and Mn are dissolved; A step of adding the solution to an alkaline solution to precipitate hydroxide; A step of collecting a precipitate from the alkaline solution; A step of mixing the precipitate and a raw material containing Li to obtain a first mixture; a first firing step of firing the first mixture; A step of mixing a raw material containing an element represented by M with the fired first mixture to obtain a second mixture; and a second firing step of firing the second mixture, Wherein, M is at least one element selected from Ti, Zr, Ta, Pr, K, La, Ba, Y, Sr, Ce, Se, Hf and Rh.